JS Printer Center (Printing Service) / Jeanttie Samban Jelani - Jelani, Jeanttie Samban (2022)
For starters, I was given a task of running a business as a part of my assignment project. As a result, I decided to open a small business which was printing servjce. I decided to do this business because I stay at hostel and there are many other students will wanted to use my service. Printing service at student center in UITM Kota Samarahan Campus 2 was closed since Covid-19 until now. This business can be done by any individual who wants to start a business of an entrepreneur. The modal to start this business does not require a lot of capital which is RM374. While running this business I also gained some experience that can be used to run business activities in the future. A positive start motivated me to venture into this field of entrepreneurship. My thanks are also dedicated to everyone who supported this effort. Unwavering support for this also proves that the buyer's trust in the seller is very high. Thus, I decided to continue being in this business as it brought me so much benefits and helping the customers by starting this service.